IMPROVING THE QUALITY OF TEACHING LEARNING PROCESS OF WRITING CLASS THROUGH LESSON STUDY - Mariana, Lina -; Nurhajati, Diani (Universitas Nusantara PGRI Kediri, 2015)
AbstractLesson Study (LS) is a professional development process that Japanese teachers engage into systematicallyexamine their practice, with the goal of becoming more effective. In the application teachers or lecturers mustalways improve the quality of teaching learning process that covers preparing syllabus and lesson plan,creating conducive classroom atmosphere and carrying assessment. They can do by cooperating with theircolleagues to reach better results. Many teachers are satisfied with the results of teaching learning process. Infact, there are many weaknesses that they do not realize. This research was carried out to answer thequestion: How does LS improve the quality of teaching learning process of writing class? The results provethat there are a lot of improvements on writing class, e.g. the materials are more challenging, the students aremore actively involved during the interaction, the lecturer has more open to receive critics from her colleague,and the students get better achievement in writing.